Andreev reflection study of a new magnetic superconductor Mo3Sb7 in magnetic field - Dmitriev, V.M.; Rybaltchenko, L.F.; Ishchenko, L.A.; Khristenko, E.V.; Bukowski, Z.; Troć, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Andreev reflection in contacts based on a magnetic superconductor Mo3Sb7 in magnetic field has been investigated by the point-contact method. It is found that the behavior of the order parameter in the magnetic field D(H) is essentially dependent on the value of D, which varies widely (D(0,0)≈0.01-0.31meV) for different contacts at practically invariant Tc. At high D the dependence Dmax(H) deviates slightly from the theoretical prediction applicable under the point-contact conditions. As the order parameter decreases, the deviation starts to increase and becomes very large when D approaches its minimum. Proceeding from the resultsobtained in this study and from the temperature measurements on Mo3Sb7 performed formely, we are inclined as before to assign the compound to the class of superconductors with the anisotropic gap function. So, it in no way can be considered as an conventional BCS-type superconductor. The upper critical fieldHc2 ≃ 16.5 kOe found here is close to that obtained from magnetization measurements in other study. According to the estimation performed, the pair-breaking effect of the Pauli paramagnetism is rather weak inMo3Sb7.